Afterburn - Harrison, Colin, 1960- (New York : St. Martin's Paperbacks, 2001)
With his family in danger of dying out--the son is dead, the daughter is infertile and the wife is on the verge of Alzheimer's--a millionaire searches for a woman who will give him an heir. In this way, high-flying businessman Charlie Ravich meets Christina, a gangster.
Keywords: Executives -- Fiction; Ex-convicts -- Fiction; Organized crime -- Fiction; Hong Kong (China) -- Fiction; New York (N.Y.) -- Fiction; Suspense fiction